PEMANFAATAN LIMBAH INDUSTRI SANDAL SEBAGAI AGREGAT DALAM CAMPURAN SEMEN PUTIH UNTUK PEMBUATAN ORNAMEN PENGGANTI BATU ALAM - Wiwik Purwiningsih (Purifikasi, 2006)
Sandal waste represents the residual peoduct, which is piled cumulatively in the residential areas around the factory. This fact becomes a consideration to use the waste for a particular purpose. This situation can be connected to the existence of interior and exterior ornament business where the waste can be used as raw material. This study was aimed to utilize the sandal waste as an aggregate, which is mixed with white cement, in order to replace of the natural stones. The method included trial tests of mixtures in different compositions, followed by comparisons of results according to visual performance and compression test. Results of this study showed that the best mixture was observed in cement and waste composition ratio of 1:3. At this composition, the aggregate was visually very good, easy to process, and save the use of cement. From the economical point of view, the use of sandal waste as described in this study, could provide an added value for the waste generator and a new employment opportunity.